2009
DOI: 10.1016/s1658-3876(09)50024-6
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial sepsis-induced late onset thrombocytopenia in a neonatal tertiary care unit

Abstract: LOS sepsis is an important risk factor for thrombocytopenia in the NICU. Fungal and gram- negative sepsis are frequently associated with a decreased platelet count. Sepsis-induced thrombocytopenia is more common among LBW babies and preterm babies. The mortality rate is significantly related to degree of thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
9
25
1
Order By: Relevance
“…This has been shown in other studies as well. 8 Thrombocytopenia occurs more frequently in association with certain factors like sepsis, ELBW, severe birth asphyxia, babies born to pre-eclamptic mothers and low birth weight babies and this was seen in our study as well. Though it is less common in babies with meconium aspiration, hyper bilirubinemia, mild birth asphyxia and respiratory distress syndrome, in our study moderate thrombocytopenia was found in 13.0% cases (16/115) and severe thrombocytopenia was found in 2.6% (3/115) in this group as well.…”
Section: Discussionsupporting
confidence: 81%
“…This has been shown in other studies as well. 8 Thrombocytopenia occurs more frequently in association with certain factors like sepsis, ELBW, severe birth asphyxia, babies born to pre-eclamptic mothers and low birth weight babies and this was seen in our study as well. Though it is less common in babies with meconium aspiration, hyper bilirubinemia, mild birth asphyxia and respiratory distress syndrome, in our study moderate thrombocytopenia was found in 13.0% cases (16/115) and severe thrombocytopenia was found in 2.6% (3/115) in this group as well.…”
Section: Discussionsupporting
confidence: 81%
“…7 Studies conducted by Charoo BA et al and Robert and Murray1 also state that neonatal thrombocytopenia was more common among low birth weight babies. 18 Gupta AK et al stated that LBW babies showed statistically significant thrombocytopenia due to their limited ability to compensate for accelerated destruction of platelets. 19 Placental transport of IgG from maternal to fetal circulation increases with maturity and this transport is hampered in low birth weight babies which make them more prone for sepsis.…”
Section: Neonatal Factorsmentioning
confidence: 99%
“…In studies conducted by Nandyal et al, Charoo BA et al, prematurity was associated with severe thrombocytopenia. 4,10,18 Among multiple neonatal risk factors, sepsis was the most commonest cause of neonatal thrombocytopenia which was found in 97 (48.5%) babies and was associated with severe neonatal thrombocytopenia. The percentage of sepsis among thrombocytopenic babies in nandyal et al study was 22.2%, Gupta et al study was 42% and khalessi et al study was 24.1%.…”
Section: Neonatal Factorsmentioning
confidence: 99%
“…No significant differences were seen in platelet and platelet indices in relationship with gestational age. [6][7][8][9][10][11][12][13][14] There is paucity of literature on this role of platelet parameters in neonatal sepsis in Indian subcontinent. This study was done for evaluation of platelet indices (platelet count, PDW, MPV) in neonatal septicaemia, in rural Indian population.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have documented significant changes in platelet indices in neonatal sepsis as well as older children and adults. [6][7][8][9][10][11][12][13][14][15][16][17][18] Still, there is no clear consensus, so more studies are needed on this subject. At present, there is paucity of literature regarding platelet indices in neonatal sepsis.…”
Section: Introductionmentioning
confidence: 99%